Different hosts in different lakes: prevalence and population genetic structure of plerocercoids of Ligula intestinalis (Cestoda) in Czech water bodies - Nazarizadeh, Masoud; Peterka, Jiří; Kubečka, Jan; Vašek, Mojmír; Jůza, Tomáš; de Moraes, Karlos Ribeiro; Čech, Martin; Holubová, Michaela; Souza, Allan T; Blabolil, Petr; Muška, Milan; Tsering, Lobsang; et al. (Folia parasitologica, 2022)
Ligula intestinalis (Linnaeus, 1758) is a tapeworm parasite with a worldwide distribution that uses a wide variety of fish species as its second intermediate host. In the present study, we investigated the prevalence and population genetic structure of plerocercoids of L. intestinalis in five common cyprinoid species, roach Rutilus rutilus (Linnaeus), freshwater bream Abramis brama (Linnaeus), white bream Blicca bjoerkna (Linnaeus), bleak Alburnus alburnus (Linnaeus), and rudd Scardinius erythrophthalmus (Linnaeus), collected in six water bodies of the Czech Republic (Milada, Most, Medard, Jordán, Římov and Lipno). Of the six study sites, the highest frequency of parasitism was recorded in Lake Medard (15%). The overall prevalence rate among the species was as follows: roach > rudd ≥ freshwater bream > bleak > white bream. Two mitochondrial genes (cytb and COI) were used to compare the population genetic structure of parasite populations using selected samples from the five fish species. The results of the phylogenetic analysis indicated that all populations of L. intestinalis were placed in Clade A, previously identified as the most common in Europe. At a finer scale, haplotype network and PCoA analyses indicated the possible emergence of host specificity of several mtDNA haplotypes to the freshwater bream. Moreover, pairwise Fixation indices (FST) revealed a significant genetic structure between the parasite population in freshwater bream and other host species. Parasite populations in roach not only showed the highest rate of prevalence but also depicted a maximum number of shared haplotypes with populations from bleak and rudd. Our results suggest that recent ecological differentiation might have influenced tapeworm populations at a fine evolutionary scale. Thus, the differences in prevalence between fish host species in different lakes might be influenced not only by the parasite's ecology, but also by its genetic diversity.
Keywords: Animals; Fish Diseases; interakce hostitele a parazita; Cestoda; Host-Parasite Interactions; jezera; Genetic Structures; mitochondriální DNA; fylogeneze; Prevalence; Genetics, Population; genetické struktury; Cyprinidae; DNA, Mitochondrial; Phylogeny; Czech Republic; paraziti; Parasites; Cestode Infections; zvířata; cestodózy; Lakes; nemoci ryb; Česká republika; voda; prevalence; Water; populační genetika